2018
DOI: 10.1080/21501203.2017.1423127
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation and characterisation of the orange pigment produced by a cold adapted strain of Penicillium sp. (GBPI_P155) isolated from mountain ecosystem

Abstract: With globalisation and growing health risks of synthetic colourants, search for pigments from natural sources has increased owing to their non-toxic nature. The present study highlights the bioprospection of natural pigment from a cold adapted fungal strain of Penicillium sp. (GBPI_P155), isolated from soil of Indian Himalayan region. The fungus produced insoluble and orange-coloured pigment in liquid medium with maximum production recorded in potato dextrose (PD) broth at 15°C and 3 pH, while maximum biomass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 39 publications
0
34
0
Order By: Relevance
“…(GBPI_P155) isolated from the high altitude soil of Indian Himalayan region was reported to produce dark orange pigment. This extracted pigment was also found to be active against actinobacteria and several Gram-positive and Gram-negative bacteria (Pandey et al, 2018).…”
Section: Terrestrial Sediments and Soilmentioning
confidence: 94%
“…(GBPI_P155) isolated from the high altitude soil of Indian Himalayan region was reported to produce dark orange pigment. This extracted pigment was also found to be active against actinobacteria and several Gram-positive and Gram-negative bacteria (Pandey et al, 2018).…”
Section: Terrestrial Sediments and Soilmentioning
confidence: 94%
“…luteoride D and pseurotin G) in the fungus. [Color figure can be viewed at wileyonlinelibrary.com] Sasidharan et al, 2015;Pandey et al, 2018). Joyner et al (2010) reported that oral pathogen S. mutans produces mutanobactin A, that is not only a stress-resistance factor for the bacterium but it has also been found to regulate cross-kingdom interaction by inhibiting the yeastmycelium transition of C. albicans (Joyner et al, 2010;Wu et al, 2010).…”
Section: Chemical Signals Involved In Antagonistic Interactionsmentioning
confidence: 99%
“…Bacterial and fungal SMs are well known to exhibit multiple functions as antimicrobial, anticancer and antioxidant agents (Venil et al ., 2013; Tuli et al ., 2015; Narsing Rao et al ., 2017). In addition to a developmental role in the producing microbe some SMs also provide protection against harmful competitors in a BFI due to their antibiotic properties (Mangan, 1969; Visalakchi and Johnpaul, 2010; Sasidharan et al ., 2015; Pandey et al ., 2018). Joyner et al .…”
Section: Small Signalling Molecules‐mediated Bfis In Disease and Healthmentioning
confidence: 99%
“…Many investigations report Penicillium as potent producers of pigment [25,61,[96][97][98], such as arpink red TM (Figure 4) [95]. A biosynthetic pathway for the yellow pigment chrysogine from Penicillium chrysogenum has been proposed recently [92].…”
Section: Fungal Species Pigments Referencesmentioning
confidence: 99%